Gerencialismo e a gestão de pessoas na administração pública federal: caso do Instituto Federal de Educação, Ciência e Tecnologia da Paraíba - Santos, Vanessa Jaqueline Ferreira dos (2023)
The management of people in the public sector is undergoing structural changes with the transformation of public administration. Thus, in its most recent phase, in the public sector, managerial policies in the area of people management in the private sector are inspired by the business logic that favors a neoliberal perspective. Among these policies, we can mention Decree No. 9,991/2019, which provides for the National Policy for the Development of People (PNDP), with a focus on managing the skills of civil servants. In the context of counter-reforms of the Brazilian State and in light of the discussion in Congress of Proposed Constitutional Amendment No. 32/2020, the administrative reform (PEC 32/2020) is proposed, among other legislative acts. In this scenario, the general objective of this study is to analyze how IFPB's personnel policies correlate with the process of reconfiguring people management in the face of the managerialism embedded in the Federal Public Administration. More specifically, we will: a) Discuss aspects of managerialism in people management policy in the context of the federal public administration; b) Problemize people management based on the National Policy for the Development of People and the Administrative Reform; c) Analyze people management at the Federal Institute of Paraíba, in line with the National Policy for the Development of People. To achieve the proposed objectives, the research had a qualitative approach, with a descriptive and exploratory nature. Regarding the methods employed, we enumerate the bibliographic and documentary method. To arrive at the results, documentary analysis was performed, based on normative documents, such as Decree No. 9,991/2019 and the National Policy for Personnel Development, which guided the way federal civil servants are managed. The results allow us to infer that people management in the public sector has adopted the managerial paradigms of the private sector, changing the conception of the common good and imposing metrics of pronounced control on workers, sometimes causing institutional harassment and the illness of civil servants. In institutions, there is a perception of dilapidation due to budget cuts promoted by the policies of dismantling the Brazilian State from 2016 onwards, based on the deepening of neoliberal logic.